The Convergence of Durand-Kerner Method for Simultaneously Finding All Zeros of the Polynomial (Journal of Computational Mathematics, 2021)
In this paper we propose the two kinds of different criteria and use them to judge the convergence of Durand-Kerner method and to compare the obtained results with other methods.